Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.3897/compcytogen.v6i1.1873
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic analysis in the incertae sedis species Astyanax altiparanae Garutti and Britzki, 2000 and Hyphessobrycon eques Steindachner, 1882 (Characiformes, Characidae) from the upper Paraná river basin

Abstract: Cytogenetic analyses were accomplished in two populations of Astyanax altiparanae Garutti & Britzki, 2000 and one population of Hyphessobrycon eques Steindachner, 1882, considered incertae sedis in Characidae family. Two populations of Astyanax altiparanae (Mogi-Guaçu and Tietê rivers) presented 2n=50, with the same karyotype formula: 6M+12SM+20ST+12A (FN=88). Hyphessobrycon eques from Capivara river presented 2n=52 and karyotype formula 14M+16SM+4ST+18A (FN=86). In each karyotype, the nucleolus organizer regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The yellow tail tetra (Astyanax altiparanae) has a wide distribution in South America (Martinez et al 2012) and therefore can be raised without the risk of introducing exotic species into the natural environment. This species has a great aquaculture potential due to its high reproductive rate, short production cycle (Porto-Foresti et al 2005) and omnivorous (Adrian et al 2001), while having a good acceptance of processed diets.…”
mentioning
confidence: 99%
“…The yellow tail tetra (Astyanax altiparanae) has a wide distribution in South America (Martinez et al 2012) and therefore can be raised without the risk of introducing exotic species into the natural environment. This species has a great aquaculture potential due to its high reproductive rate, short production cycle (Porto-Foresti et al 2005) and omnivorous (Adrian et al 2001), while having a good acceptance of processed diets.…”
mentioning
confidence: 99%
“…An interesting feature observed by C-band technique in the Hyphessobrycon eques was a heteromorphic block of heterochromatin always presents on short arm (pair 19) in all specimens (with and without B chromosomes), which another population of Hyphessobrycon eques studied by Martinez et al (2012) not showed. Nevertheless, we believe that the B chromosome (observed in two Hyphessobrycon eques females) may be related with chromosomal rearrangements (see a possible mechanism in the Figure 3).…”
Section: Discussionmentioning
confidence: 90%
“…bimaculatus showed the same diploid number (2n=50) but with differences in the karyotype formulas, probably due to rearrangements such as pericentric inversions. This last group, unlike the "scabripinnis group", has shown a constancy in the diploid number (Domingues et al, 2007;Pamponet et al, 2008;Ferreira Neto et al, 2009;Kavalco et al, 2011;Pacheco et al, 2011;Peres et al, 2011;Martinez et al, 2012), indicating an evolutionary karyotype pattern relatively more conserved than that of the "scabripinnis complex". In turn, the distinct karyotypes presented by the two populations of A. asuncionensis also show the occurrence of two karyomorphs and a probable "asuncionensis complex."…”
Section: Discussionmentioning
confidence: 99%